PRINSIP EQUILIBRIUM ANTARA NILAI MATERIALISME DAN SPIRITUALISME SISTEM PRODUKSI DALAM EKONOMI ISLAM - Misbahul Ali; Rahwan (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2020)
Production is the process of producing goods and services or the process of increasing the value of an object. In Islam production has the aim of creating optimum maṣlaḥah for humans as a whole. With this optimum maṣlaḥah, falāh will be achieved which is the ultimate goal of economic activity as well as the purpose of human life. The purpose of this study is to describe the construction of the production system in the Islamic economy, and to describe the principle of equilibrium between the value of materialism and the spiritualism of the production system in the Islamic economy. The results of this study indicate that the production system in the Islamic economy is a conceptual framework that is based more on maintaining ethical-religious values ​​by prioritizing efforts to realize the value of justice and humanity in meeting the needs of human life. At the operational level, the Islamic production system seeks to integrate equally between efforts to obtain material profit (profit) with the spirit to manifest divine values ​​through service activities in providing goods of necessity, in order to realize mutual prosperity among fellow human beings.